ANALISIS HUBUNGAN ANTARA KARAKTERISTIK USAHA DENGAN KEEFEKTIFAN JARINGAN KOMUNIKASI AGRIBISNIS IKAN HIAS (KASUS DI KABUPATEN BOGOR, JAWA BARAT) - SUCI INDRANINGSIH, KURNIA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 2 Juli 2004, 2012)
The research was designed to comprehend the effectiveness of agribusiness communication network of ornamental fish farmers, and correlations of business characteristics to effectiveness of agribusiness communication network. This research was conducted in July-August, 2001 in sub-districts Ciampea and Parung, Bogor, West Java. Sixty farmers were randomly sampled during the survey. The Tau-b Kendall (?) correlation statistics was used in the data analyses. The results indicated that agribusiness communication network was not effective, effective only at business aspect. The laborer, and input ownership were related to effectiveness of agribusiness communication network.
Keywords: Ornamental Fish, Effectiveness, Communication Network